(untitled) (Swiss Medical Weekly, 2021)
AIMS To identify the incidence of iatrogenic events leading to paediatric intensive care unit (PICU) admission and to analyse these patients regarding demographic, illness severity and outcome parameters. MATERIAL AND METHODS This was a retrospective case series. The computerised charts of all patients admitted to the multidisciplinary, tertiary, 18-bed PICU in 2014 were analysed. Iatrogenic events leading to PICU admission were identified and their preventability assessed. Underlying diseases, causes of iatrogenic events, illness severity at PICU admission, presence of complex chronic conditions, patient origin, length of stay on the PICU and outcome were analysed. RESULTS There were 138 admissions associated with iatrogenic events out of 1102 admissions (12.5%). Ninety iatrogenic events led to unplanned admissions and 48 cases concerned scheduled admissions, where the iatrogenic event would have led to PICU admission by itself or caused a second, planned PICU admission for re-operation. Iatrogenic complications during surgery (31% of all iatrogenic events), wrong management decisions / delayed diagnoses (20%) and nosocomial infections (14%) were the categories most often involved. Regarding origin of the patients, the greatest difference between iatrogenic event admissions and non-iatrogenic event admissions was found for the ward (21% vs 11%). The patients admitted for iatrogenic events had a higher mean expected mortality (8.4 vs 4.7%, p = 0.02) and a higher observed PICU mortality (5.8 vs 3.3%, p = 0.15). Of all iatrogenic events, 60.1% were judged to be preventable. The highest preventability rate was found in the categories “nosocomial infections” (100%) and “management decisions / delayed diagnoses” (92.9%). CONCLUSION In our setting, the number of PICU admissions associated with iatrogenic events is significant and comparable to adult data on admission to ICU caused by iatrogenic events. The categories with most potential for improvement are nosocomial infections and the wrong management decisions / delayed diagnoses. Focused measures on these iatrogenic events may have a major impact on patient outcome, availability of PICU resources and healthcare costs.